Nazwy Wilna i jego mieszkańców w dokumentach Wielkiego Księstwa Litewskiego (WKL) - Leszek Bednarczuk (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2010)
The author of the article discusses names of Wilno/Vilnius in the oldest Latin, Russian and Polish documents. He also analyses place names denoting the city, city districts, suburbs, streets and alleys, castles, towers, mountains, as well as names denoting inhabitants of city and region.